Diffractive Synthesis of Multipole Interference States Using Low‐Index Mesoscale Dielectric Structures - Rabiul Islam Sikder; Myung Gi Ji; Jaeyoun Kim (Advanced Photonics Research)
The multipole interference (MPI) effect plays pivotal roles in the formation of electromagnetic responses in various settings. In the optics regime, it has been realized typically through the Mie resonance that necessitates high‐index, deep‐subwavelength‐scale dielectric resonators that are challenging to fabricate. Herein, a new, diffraction‐based MPI scheme that can be realized with low‐index, mesoscale dielectric structures is demonstrated. It is verified that this “diffractive MPI” concept by realizing various MPI states using micrometric polymeric cuboids fabricated by soft‐lithography. Subsequent analyses reveal that the MPI states with a distinct near‐zero forward scattering (NZFS) characteristic played crucial roles in shaping the cuboid's transmission spectrum. A hitherto unreported NZFS state, which exhibits a unique, “trifolium” radiation pattern, is also identified. The spectral position of such NZFS states turns out to be strongly dependent on the cuboid's geometry. By combining these results, the diffractive NZFS formation is related to the important phenomena of induced transparency and structural color generation.